Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd001888.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cell salvage for minimising perioperative allogeneic blood transfusion

Abstract: Trusted evidence. Informed decisions. Better health. Cochrane Database of Systematic Reviews Analysis 3.6. Comparison 3 Cell salvage-blood transfused (active versus control), Outcome 6 Units of allogeneic blood transfused (Active vs Control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 90 publications
6
179
0
6
Order By: Relevance
“…This technique is known as autologous blood cell salvage and it has been shown to be effective in reducing allogeneic transfusion. 52,53 The technique is generally safe, although concerns have been raised regarding the possibility of reintroducing unwanted cells or materials (eg, tumor cells, fat droplets, amniotic fluid, bacteria, or pharmaceutical agents present in the surgical field) into the blood circulation during the procedure. 54,55 However, published case reports and studies have not indicated a significant risk with the use of currently available cell salvage systems.…”
Section: Intraoperative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is known as autologous blood cell salvage and it has been shown to be effective in reducing allogeneic transfusion. 52,53 The technique is generally safe, although concerns have been raised regarding the possibility of reintroducing unwanted cells or materials (eg, tumor cells, fat droplets, amniotic fluid, bacteria, or pharmaceutical agents present in the surgical field) into the blood circulation during the procedure. 54,55 However, published case reports and studies have not indicated a significant risk with the use of currently available cell salvage systems.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…61,62 Overall, intraoperative cell salvage remains a safe and effective technique in reducing allogeneic transfusions and improving patient outcomes. 17,53 On the other hand, acute normovolemic hemodilution relies on removing a part of the blood volume from the circulation and replacing it with other fluids (crystalloids or colloids) before bleeding takes place. Therefore, the blood lost during the surgery is diluted, and the total amount of blood loss from the surgical wound is reduced.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…conclude in their systemic review that cell salvage is an effective tool to reduce the need for allogeneic blood transfusion in both cardiac and orthopaedic surgery. They state however that many studies may have been biased and are therefore difficult to interpret (Carless et al, 2010). It is stated that intra-operative cell salvage is beneficial in surgery when blood loss exceeds 1,000 ml (Lemaire, 2008;Sculco, 1995).…”
Section: Washed Autologous Transfusionmentioning
confidence: 99%
“…here is some evidence that cell-saving devices (CS) reduce red blood cell (RBC) transfusion during cardiac surgery, but that extensive use of a CS may lead to a bleeding diathesis [1,2]. Two recent meta-analyses [3,4] suggest that fewer patients receive allogeneic blood transfusions when a CS is used. However, there was substantial heterogeneity as a result of different bloodconservation concepts of the included studies, and most studies were underpowered with methodological shortcomings.…”
mentioning
confidence: 99%